Department of anesthesiology and reanimation, school of medicine, Marmara University, Istanbul, turkey - Umuroğlu, Tümay; Eti, Zeynep; Takıl, Arzu; Göğüş, Yılmaz (My University, 2002)
Objective: The aim of this prospective and randomized study was to compare the methods used for the assessment of the nasoduodenal tube position in critically ill patients according to the success rate, time spent on successful placement and cost effectivity. Methods: Sixty critically ill patients for whom enteral feeding with nasoduodenal tube (ND) was planned, were allocated randomly into 3 groups. The assessment of the location of the ND tube was done by auscultation of the loudest sound location over the right flank in group A, pH determination of the duodenal aspirate in group PH and fluoroscopic view in group F. The failure criteria was the placement of a ND tube in the stomach in all groups, the necessity of having more than two flat abdominal radiographs in group A and PH, the duration of fluoroscopy for more than 10 minutes in group F. The success rate, the time of successful placement and the total cost were determined and compared statistically by using analysis of variance and Fisher’s Exact Test. Results: The success rate was significantly higher in group F (95%). The time of successful placement was significantly shorter in group F (75.15 ± 5.32 min versus 147.95 ± 77.05 min in group A and 177.75 ± 154.84 min in group PH). There was no difference between groups regarding the total cost. A 25% false positive result was found in the PH group i.e. the tube was found to be in the stomach after the radiological evaluation although pH values were > 4. Conclusion: For critically ill patients in whom enteral feeding is planned with ND, fluoroscopy should be preferred whenever possible for the placement of the ND tube because the success rate is higher, the placement is quicker and it is more cost-effective than the conventional methods.
Keywords: Enteral nutrition, Enteral tube insertion, Fluoroscopy.